What is the impact of tour guide quality and outdoor activity innovation on tourist satisfaction in Bali? - Abas, Sayid; Nurhasanah, Dila Padila; Lesmana, Tera (West Science Interdisciplinary Studies, 2025)
This study examines the impact of tour guide quality and outdoor activity innovation on tourist satisfaction in Bali, a premier global tourist destination. Utilizing a quantitative approach, data were collected from 150 tourists using a structured Likert-scale questionnaire (1–5). Data analysis was performed using SPSS version 25, involving descriptive, reliability, and regression analyses. Results reveal that both tour guide quality and outdoor activity innovation significantly and positively influence tourist satisfaction, with tour guide quality exhibiting a stronger impact. The findings highlight the critical role of professional, knowledgeable guides and innovative recreational offerings in shaping memorable tourist experiences. This study provides actionable insights for tourism stakeholders in Bali, emphasizing the importance of investing in guide training programs and creative outdoor activities to sustain and enhance tourist satisfaction in a competitive global market.